Sex differences in pulmonary function during exercise - Harms, C. A.; Rosenkranz, S. (Medicine & Science in Sports & Exercise, 2008)
Structural and hormonal sex differences are known to exist that may influence the pulmonary system's response to exercise. Specifically, women tend to show reduced lung size, decreased maximal expiratory flow rates, reduced airway diameter, and a smaller diffusion surface than age- and height-matched men. Additionally, ovarian hormones, namely progesterone and estrogen, are known to modify and influence the pulmonary system. These differences may have an effect on airway responsiveness, ventilation, respiratory muscle work, and pulmonary gas exchange during exercise. Recent evidence suggests that during exercise, women demonstrate greater airway hyperresponsiveness and expiratory flow limitation, increased work of breathing, and, perhaps, greater exercise-induced arterial hypoxemia compared with men. The consequence of these pulmonary effects may influence exercise capacity.